The molecular characterization of the clumping Factor A (ClfA) from Staphylococcus aureus using monoclonal antibodies - McNamara, Gillian (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2000)
Clumping factor (ClfA) of Staphylococcus aureus is the major fibrinogen- binding adhesin located on the cell surface of the bacterium. Monoclonal antibodies (mAbs) were produced to two recombinant truncated ClfA proteins, fibrinogen-binding Clf33 (221-550) and non-fibrinogen-binding Clf42 (332-559). Three mAbs, two against C103 (221-550) (mAbs 36 and 47) and one against Clf42 (332-559) (mAb6) which inhibited the ClfA-fibrinogen interaction were characterized. Each mAb was shown to be specific in recognising ClfA on ELISA. These mAbs inhibited bacterial clumping in soluble fibrinogen and bacterial adherence to solid-phase fibrinogen. Two of these mAbs, 36 and 47, inhibited clumping and adherence synergistically. This antibody combination also blocked S. aureus binding to platelet-fibrin clots in vitro. The synergistic mAbs 36 and 47 were also tested in a mouse renal infection virulence model. Using Western immunoblotting of recombinant ClfA truncates, inhibition of mAb binding to Clf41 (221-559) with soluble peptides, binding analysis of ClfA site-directed mutant proteins, and reactivity with ClfA-fibrinogen and ClfA-fibrinogen y-chain 396- 412 complexes, these mAbs were shown to define epitopes on ClfA which are functionally important in the fibrinogen-binding mechanism.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin